ANALISIS TINGKATAN STRES DAN PENGARUHNYA TERHADAP KINERJA PIMPINAN CABANG BANK SWASTA NASIONAL DI SURABAYA - Purnomolastu, N. (Journal of Management and Business, 2004)
After facing some problems for the last few years and along with the monetary crisis in Indonesia, now days, especially concerning with the top management of bank, in running banking activities comes to surface. The activities are close to demand/ target assigned to them which surely affects their stress level. In the end, it also affects their performance. This research was conducted in June 2003 to private bank in Surabaya that enter into an alliance with "Perbanas" (National Private Bank Association). It aimed at knowing to what extend the level of stress undergone by the bankers and its impacts upon it. The research was conducted to 51 banks its recorded in “Perbanas" secretariat by means of list of questions. The list had been standardized and formulated through scoring of stress level and the degree offreedom 5% Chi-Square (Q2) with out. if the were the impacts of the stress level